The effects of traditional Chinese medicine combined with chemotherapy on immune function and quality of life in patients with non-small cell lung cancer: A protocol for systematic review and meta-analysis. Issue 45 (6th November 2020) - Zhao, Li-Na; Yang, Yin-Qing; Wang, Wen-Wen; Li, Qian; Xiao, Hua
Abstract: Background: This article will evaluate the effects of traditional Chinese medicine (TCM) combined with chemotherapy on the immune function and quality of life of patients with non-small cell lung cancer (NSCLC), and evaluate the published side effects. Methods: The systematic review and meta-analysis will be conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. The databases we will search include: PubMed, EMBASE, Cochrane Library, Web of Science, China National Knowledge Infrastructure, China Biomedicine, Wan fang Data, and Technology Periodical Database. The search date is from inception to June 30, 2020. There are no restrictions on the document language. The literatures included in this study are randomized controlled trials. The main results include ratio of CD3 +, CD4 +, CD8 +, CD4 + /CD8 +, NK cells, the level of IgA, IgG, IgM, and Karnofsky performance status score. The secondary result is to evaluate various side effects during treatment. We will use the Cochrane Collaboration tool to evaluate each study and use Review Manager software (RevMan, version 5.3) to merge and analyze the data. The 2 researchers will independently cross-screen the literature, extract data, and evaluate the quality. If there are differences, we will resolve them through discussion or consultation with a third reviewer. Results: The results of this study will provide high-quality evidence for the effect of TCM combined with chemotherapy on the immune function and quality of life of patients with NSCLC. Conclusion: This article will comprehensively evaluate the effects of TCM combined with chemotherapy on the immune function and quality of life of patients with NSCLC, and provide evidence-based evidence for clinical practice. Ethics: Since the data used in this study is based on previous trials and does not involve patient privacy, ethical approval is not required. Study registration number: INPLASY202070071